2015
DOI: 10.1118/1.4905233
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a 2D diode array in “magic phantom” for use in high dose rate brachytherapy pretreatment quality assurance

Abstract: . (2015). The evaluation of a 2D diode array in "magic phantom" for use in high dose rate brachytherapy pretreatment quality assurance. Medical Physics, 42 (2), 663-673.The evaluation of a 2D diode array in "magic phantom" for use in high dose rate brachytherapy pretreatment quality assurance Abstract Purpose: High dose rate (HDR) brachytherapy is a treatment method that is used increasingly worldwide. The development of a sound quality assurance program for the verification of treatment deliveries can be chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…The measured dwell position deviations of our systems are comparable with those from systems based on silicon diode and IC array. 18,31,34 The dwell time deviations are also comparable with those from systems based on silicon diode. 18,31 In terms of functionality, our systems allow not only dwell position and time verification but also source activity monitoring for HDR-BT QA (and in vivo QC with the instrumented applicator).…”
Section: F Comparison With Literaturesupporting
confidence: 58%
See 2 more Smart Citations
“…The measured dwell position deviations of our systems are comparable with those from systems based on silicon diode and IC array. 18,31,34 The dwell time deviations are also comparable with those from systems based on silicon diode. 18,31 In terms of functionality, our systems allow not only dwell position and time verification but also source activity monitoring for HDR-BT QA (and in vivo QC with the instrumented applicator).…”
Section: F Comparison With Literaturesupporting
confidence: 58%
“…one hand, the measured results are compared with planned data on dwell position and dwell time. On the other, we propose to adopt a modified gamma index (MGI) in dwell position and time based upon the original concept proposed by Espinoza et al 31 In the formalism of Espinoza, the gamma index for each measured dwell position is calculated over all planned dwell positions in the treatment protocol, and a pass/fail decision is made upon its minimum value (passed if the minimum gamma index is lower than unity). However, for early error detection, the modified gamma index is calculated on sequentially paired dwell positions in measured and planned datasets.…”
Section: G Evaluation Of Precision Of Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has shown that similar source position verification accuracy to EPIDs may be achieved with the MP system. Furthermore, the MP system has been shown to have a superior timing resolution of less than 1 ms . As such, the MP delivers a dedicated, inexpensive HDR brachytherapy in vivo source position verification system with superior timing resolution that can easily be mass produced and is practical for routine clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to investigate the feasibility of using a two‐dimensional (2D) diode array, the “Magic Plate” (MP), developed at the Centre for Medical Radiation Physics (CMRP), University of Wollongong (UoW), Australia, for in vivo source position verification of a HDR prostate brachytherapy treatment. Previous studies performed with the MP in homogeneous phantom media and have reported source localization accuracy of less than 1 mm and temporal resolution of 1 ms, making it an ideal device for real‐time source position verification. It is hypothesized that the introduction of heterogeneous media associated with the patient geometry may compromise the accuracy of source localization using this device.…”
Section: Introductionmentioning
confidence: 99%